2007
DOI: 10.1016/j.rapm.2007.06.394
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lateral Block of the Suprascapular Nerve: A Safe Approach and How Much to Inject? A Morphological Study

Abstract: Based on this cadaver study, the lateral modified approach appears to be a safe technique for a suprascapular nerve block, which might be preferred as a single shot technique. A 5 mL volume appears sufficient to fill the supraspinous fossa and to reach the suprascapular nerve, which branches in this anatomical compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 14 publications
2
35
0
5
Order By: Relevance
“…Too low a volume will result in maldistribution and too high will result in the spread of local anesthetic to the brachial plexus. 9 A recent CT scan study showed that a 10 mL injectate spread to the brachial plexus within the axilla in three out of 33 cadavers. 9 The authors suggested that 5 mL is the adequate volume for injection into the suprascapular fossa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Too low a volume will result in maldistribution and too high will result in the spread of local anesthetic to the brachial plexus. 9 A recent CT scan study showed that a 10 mL injectate spread to the brachial plexus within the axilla in three out of 33 cadavers. 9 The authors suggested that 5 mL is the adequate volume for injection into the suprascapular fossa.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent CT scan study showed that a 10 mL injectate spread to the brachial plexus within the axilla in three out of 33 cadavers. 9 The authors suggested that 5 mL is the adequate volume for injection into the suprascapular fossa. One concern of using such a low volume is the maldistribution and potential decrease in the duration of the blockade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the Dangoisse, 20 Checcucci, 11 and Feigl 25 techniques are less likely to result in such complications, as they do not access the scapular notch where the suprascapular nerve enters after passing below the upper transverse ligament, in addition to the fact that the needle insertion position is far from the lung.…”
Section: Feigl 25mentioning
confidence: 99%